The effectiveness of sight-singing and the perception towards performance development for voice students at UiTM Faculty of Music / Sharifah Fadilatul A'ina Syed Alias - Syed Alias, Sharifah Fadilatul A'ina (2019)
Sight-Singing skill is importance for music students, it helps students in development and improvement towards performance and musicality. This research is focuses on Degree voice students of Faculty of Music in UiTM Shah Alam, to find out the effectiveness of sight-singing and the perception taken by them towards sight-singing This research would be looking based on three main objectives which is to encourage music students who are majoring in voice students practice their sight-singing, to find out the factor why some of voice students weak in sight-singing and to investigate the effectiveness of sight-singing for voice students. This research will be helpful and useful for voice students who interested to know the effectiveness of sight-singing and what sight-singing can help them to become a good singer and musician as well. The findings of this study can be the guideline for voice students to know the ability in sight-singing is important and how it related to performance development. The findings will also find out the reason why some of voice students weak in sight-singing and also the perception taken by them towards performance development.